Upregulation of Tyrosine Kinase TKT by the Epstein-Barr Virus Transactivator Zta - Lu, Jean (American Society for Microbiology, 2000)
The Zta protein is a key transactivator involved in initiating the Epstein-Barr virus (EBV) lytic cascade. In addition to transactivating many viral genes, Zta has the capacity to influence host cellular signals by binding to promoter regions or by interacting with several important cellular factors. Based on the observation that tyrosine kinases play central roles in determining the fate of cells, a kinase display assay was used to investigate whether cells expressing Zta have an altered pattern of kinase expression. The assay revealed that TRK-related tyrosine kinase (TKT) is expressed at significant levels in Zta transfectants but not in control cells. Additional evidence was obtained from Northern and Western blotting. Importantly, the upregulation of phosphorylated TKT and TKT downstream effector matrix metalloproteinase 1 in Zta transfectants hinted that TKT might initiate a signaling cascade in Zta-expressing cells. In addition, deletion analysis of the Zta protein revealed that the transactivation and dimerization domains were both essential for the upregulation of TKT transcription. Moreover, correlation of expression levels of Zta and TKT transcripts in nasopharyngeal carcinoma biopsy specimens was clearly demonstrated by quantitative PCR (Q-PCR), which provides the first evidence for an effect of Zta on cellular gene expression in vivo. These findings offer insight into the virus-cell interactions and may help us elucidate the role of EBV in tumorigenesis.